A avaliação da oralidade em contexto de formação de professores de inglês com instrução baseada em conteúdo: critérios e instrumentos - Oliveira, Thiago Alcebíades (Universidade Federal de São Carlos, 2019)
The implementation of content-based instruction (CBI), a pedagogical content/language integrating approach, has been recommended by specialists as an alternative for the development of students’ oral ability (OA) in English as foreign language (EFL) undergraduate courses for teaching credentials. However, references for the development of performance tests that could base formative assessment regarding language/content integration have not been verified in the literature. It is believed that this incipiency has led to the adaptation of proficiency tests concepts upon considerably experimental basis. The present ethnographic study aimed at describing instruments and criteria to OA assessment at an OA development subject at an EFL undergraduate course for teaching credentials at a public federal university in São Paulo state, Brazil. Data was gathered throughout 1 term with the deployment of observation, questionnaires and interviews to further investigate the assessment practices of the professor in charge of the subject as well as the test takers attitudes. One of the main goals was to be able to identify and describe the professor’s criteria to the subject’s assessment routine that could eventually suit similar contexts. The results showed that presentations, interviews and podcasts are efficient instruments for OA performance testing in CBI contexts. Such instruments, however, also demonstrated to be impractical when few examiners are recruited which, in the case of this study, led to the employment of communicative language use criteria, rather than the employment of assessment scales. In this particular context, the feedback unfolded as essential to a CBI formative assessment routine, but the test takers were not able to rationalize the results with which they were provided. Further investigation on the relation between test takers’ assessment beliefs and feedback quality would be fruitful.
Keywords: CBI; Avaliação formativa; Teste de desempenho; Habilidade oral; Formação de professores; CBI; Formative assessment; Performance test; Oral ability; Teachers education; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA